Moses among the Greek lawgivers: reading Josephus' antiquities through Plutarch's lives - Westwood, Ursula (Journal for the study of Judaism / Supplements, 2023)
"Josephus' Antiquities introduces Moses as the Jewish lawgiver, adapting the biblical account for a new audience. But who was that audience, and what did they understand by the term lawgiver ? This book uses Plutarch's Lives as an proxy for an imagined audience, providing a historically grounded but flexible model of a lawgiver, against which some of the otherwise invisible forces shaping Josephus' choices are thrown into sharp relief. This method reveals patterns of appeal and challenge in Josephus' intriguing and lively account of Moses' legislative activities"--